Pendekatan Citra Satelit Dalam Analisis Perubahan Vegetasi Di Daerah Pesisir Baurung: Satellite Imagery Approach in Vegetation Change Analysis in the Baurung Coastal Area - Chairunnisa, Chairunnisa; Nurhalisa, Nurhalisa; Najwah, Najwah; Fadilah, Elka; Maruf, Maruf; Mahful, Rafid (JURNAL HUTAN TROPIKA, 2025)
The Baurung coastal area in Majene Regency has experienced significant changes in vegetation cover due to rapid urbanization and development in the last decade, leading to a decline in green open space and the quality of coastal ecosystems. This study aims to analyze vegetation changes in the Baurung coastal area using a high-resolution satellite imagery approach combined with the Kriging spatial interpolation method. This technique produces detailed and accurate vegetation prediction maps, enabling the identification of areas experiencing degradation and areas with high vegetation cover that need to be maintained. The results indicate a significant reduction in natural vegetation with an increase in built-up areas along the coast, potentially exacerbating the risks of erosion, tidal flooding, and ecological degradation. This approach provides an important tool for adaptive and sustainable green open space management and serves as a basis for climate change mitigation policies in the Baurung coastal area.